Quality of Educational services provided in early childhood education: new looks for management practices - Moura, Irene Antonia de; Prado Sadoyama, Adriana dos Santos [UNESP] (Univ Federal Sergipe, 2017)
Social transformations have required educational institutions to provide quality services, especially in early childhood education, since this is the first phase of basic education. Analyzing this context, a research was carried out whose objective is to measure and discuss the quality of educational services offered in Early Childhood Education according to the expectation and perception of the managers, teachers and parents of the Regional Education Coordination of the Bandeirante Center of the Federal District. It is a research with a quantitative, explanatory, transversal, bibliographic, documentary, theoretical and applied approach. The legal provisions that guarantee and guide a quality school have been described; Definition of services, quality of services, educational services, expectation and perception. To perform the data collection, the SERVQUAL scale was used; The statistical software SPSS 21 was used to analyze the data. It is hoped that the obtained results will help all those involved in the educational process to perform an effective and precise administrative and pedagogical work with the intention of improving the sector that needs the most attention.
Keywords: Quality in educational services; Expectancy; Perception